Manganese-Catalyzed Enantioselective Hydrogenation of Simple Ketones Using an Imidazole-Based Chiral PNN Tridentate Ligand - Ling, Fei; Chen, Jiachen; Nian, Sanfei; Hou, Huacui; Yi, Xiao; Wu, Feifei; Xu, Min; Zhong, Weihui (Synlett, 2020)
A series of Mn(I) catalysts containing imidazole-based chiral PNN tridentate ligands with controllable ‘side arm’ groups have been established, enabling the inexpensive base-promoted asymmetric hydrogenation of simple ketones with outstanding activities (up to 8200 TON) and good enantioselectivities (up to 88.5% ee). This protocol features wide substrate scope and functional group tolerance, thereby providing easy access to a key intermediate of crizotinib.
Keywords: manganese; asymmetric hydrogenation; simple ketones; imidazole; tridentate ligand